(untitled) (Research, Society and Development, 2024)
Due to its complexity and the fact that it develops several diseases in humans, obesity must be recognized and treated as an illness. Its development may be related to the imbalance of the intestinal microbiota, where a disorder occurs in the microbiota due to the imbalance of bacterial colonization, with harmful bacteria predominant over the beneficial ones, relevant in the diagnosis of various diseases. The objective of this study was to review the findings about the relationship between the intestinal microbiota and obesity, analyzing possible changes in the microbiome of obese people. To prepare the work, files such as: scientific articles, legal documents, and magazines were used, predominantly in the database: Google Scholar, Scielo, Pubmed. Therefore, it may have a different composition in eutrophic and obese humans, as it helps and contributes to metabolism in general, playing an important role in converting food into nutrients and energy. The intestinal microbiota has been the focus of several studies that link the participation of intestinal bacteria in energy metabolism and the development of obesity. Some data prove that the arrangements of the intestinal microbiota are different in eutrophic and obese individuals; given this fact, it is believed that it participates in the process of overweight and obesity.